PENINGKATAN HASIL BELAJAR PKn DENGAN PEMBELAJARAN MODEL KOOPERATIF TIPE DUA TINGGAL DUA TAMU DI SD - MAILINDA, LILI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this rescarch was to increase the studens’ learning achievement in Civics by using Two Stay To Stray cooperative learning model in grade of SDN 17 Bonjo Alam Kecamatan Ampek Angkek. This was a classroom Action Research which applied qualitative and quantitative approaches. The subject of the research was the teacher and the students in grade V of SDN 17 Bonjo Alam Ampek Angkek. The instruments of the research wera test and observation sheet. The result of the research indicated in cycle I meeting I the students’ average score was76 and in cycle I meeting II was 80. In the second cycle their average score improved to 91. This result indicted that there was an improvement from cycle I to cycle II Key Terms : Civics Learning Achievement, Two Stay To Stray Cooperative Learning Model